Understanding Interfacial Mechanics and Mechanisms of Exfoliation and Stabilization of Graphene Using Urea/Glycerol Solvents. Issue 12 (30th September 2019) - Li, Bei; Hong, Shibo; Zhang, Xu; Xiong, Chuanxi; Zhao, Guanghui; Yang, Quanling; Liu, Hanxing
Abstract: Knowledge of interfacial mechanics and mechanisms of liquid exfoliation and stabilization of graphene in green solvents is vitally important in advancing preparation and characterization of graphene‐based materials. In this work, molecular dynamics simulations are performed to investigate exfoliation and stabilization of graphene from graphite with the assistance of urea and glycerol hybrid solvents. It is shown that the parallel exfoliation of graphene requires far less external forces as compared with the perpendicular exfoliation. Among different mediums, the 1:2 molar ratio of urea to glycerol solution presents the smallest or even negligible resistive force in both directions due to the less compressed steric hindrance to graphene exfoliation and the optimal hydrogen bonds formed between the binary solvents. During the dispersion process, the urea molecules first wedge into the graphene interlayer and then facilitate the glycerol to diffuse around or inside of the interstice due to hydrogen bonding. The confined solvents form stable layered structure to solvate and stabilize the exfoliated graphene. This work is believed to provide atomic scale understanding of interfacial mechanics and mechanisms of liquid‐phase exfoliation and dispersion of graphene and other 2D materials in low‐cost and environmental‐friendly hybrid solvents. Abstract : Interfacial mechanics and atomic understanding of liquid‐phase exfoliation and stabilization of graphene in green solvents are examined. It is shown that the 1:2 molar ratio of urea to glycerol solution presents the smallest or even negligible resistive force due to the less compressed steric hindrance to exfoliation and the optimal hydrogen bonds formed between the binary solvents.